2006
DOI: 10.1038/nprot.2006.144
|View full text |Cite
|
Sign up to set email alerts
|

A guinea pig model of acute and chronic asthma using permanently instrumented and unrestrained animals

Abstract: To investigate mechanisms underlying allergen-induced asthmatic reactions, airway hyperresponsiveness and remodeling, we have developed a guinea pig model of acute and chronic asthma using unanesthetized, unrestrained animals. To measure airway function, ovalbumin (IgE)-sensitized animals are permanently instrumented with a balloon-catheter, which is implanted inside the pleural cavity and exposed at the neck of the animal. Via an external cannula, the balloon-catheter is connected to a pressure transducer, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 32 publications
1
57
0
Order By: Relevance
“…Ressmeyer et al showed similar response between human and guinea pig lung slices to LTD4 (17). It may be reflected on the frequent use of the guinea pig as the asthma model and in leukotrienes research (25). Moreover, we revealed that LTC4 and LTD4 had the same potency for cellular proliferation through CysLT2, despite LTC4 having much higher potency for increasing intracellular calcium than LTD4.…”
Section: Intracellular Calcium Elevation Through Gpcyslt2supporting
confidence: 48%
“…Ressmeyer et al showed similar response between human and guinea pig lung slices to LTD4 (17). It may be reflected on the frequent use of the guinea pig as the asthma model and in leukotrienes research (25). Moreover, we revealed that LTC4 and LTD4 had the same potency for cellular proliferation through CysLT2, despite LTC4 having much higher potency for increasing intracellular calcium than LTD4.…”
Section: Intracellular Calcium Elevation Through Gpcyslt2supporting
confidence: 48%
“…1 and 2). Several breakthroughs in measuring lung mechanics were developed first in studies using this species, while models of the late phase response following an allergen challenge have been perfected in guinea pigs [22][23][24][25][26][27]. The emergence of transgenic mouse studies has and will continue to result in the diminished use of guinea pigs for modeling airways disease.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of transgenic mouse studies has and will continue to result in the diminished use of guinea pigs for modeling airways disease. This is unfortunate, as for many endpoints guinea pigs are superior to mice for studies of processes related to asthma and COPD [1,[27][28][29]. These advantages as well as the disadvantages of using guinea pigs to study basic processes related to asthma and COPD pathogenesis are briefly reviewed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations